Card Sort Learning Model as an Effort to Improve Student Learning Achievement in Fiqh Learning at MTs Al Ihsan Buluh Rampai - Lala Kamilatul Huda (MANDAILING GLOBAL EDUKASIA, 2025)
The issue addressed in this study is that 60% of students scored below the Minimum Mastery Criteria (KKM) in the Fiqh subject, specifically in KD 3.5, which focuses on analyzing the rules of zakat. This underperformance was linked to the use of conventional teaching methods. To address this, the study implemented an action plan consisting of two cycles, with each cycle comprising three meetings. Each meeting included introductory activities, core learning sessions, and closing reflections. This classroom action research (CAR) was supported by relevant theories and qualitative research methods, along with the necessary data collection instruments. The theoretical framework focused on zakat-related issues, while the methodology involved qualitative analysis. Observation tools were used to monitor both student behavior during the learning process and teacher performance, including lesson planning and instructional delivery. Following the two cycles and six total meetings, observational data revealed improvements in student performance. Analysis of these findings led to the conclusion that the Card Sort learning model effectively enhanced student learning outcomes. Based on these results, it is recommended that traditional teaching methods be replaced with more suitable, interactive approaches—particularly in teaching fiqh, and especially for topics such as the provisions of zakat.